Why After Fully Covid-19 Vaccinated, We are Still Obliged to Implement Health Protocols: An Evidence-Based on Agent-Based Simulation - Maghfiroh, Lutfi Rahmatuti; Tiodora Hadumaon Siagian (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2023)
Background: The current outbreak of COVID-19 affected many countries in the world, including Indonesia. The Indonesian government has taken various actions to prevent the spread of COVID-19. One of them is by applying the 3M health protocols (wearing masks, washing hands, and maintaining distance). Considering that vaccines are a critical tool in the battle against COVID-19, the Indonesian government began the COVID-19 Vaccination program on January 13, 2021. Unfortunately, many people believe that the vaccines can fully protect against COVID-19 so they are not applying the 3M health protocols anymore. Admittedly the efficiency of vaccines is not completely protective, the virus itself is still mutating and even can spread more massively. Several simulations of the spread of COVID-19 have been carried out by several researchers. However, only a few research has included variables about compliance with health protocols and vaccine programs. Objective: This study aims to provide empirical evidence for health promotion by showing why after fully COVID-19 vaccinated, people are still obliged to implement health protocols. Methods: We conducted 12 scenarios of simulations to understand the effect of complying and not complying with these two programs. Results: The simulation results show that after being fully vaccinated against COVID-19, it is proven that people are still required to implement health protocols such as wearing masks, washing hands, and practicing physical and social distancing because there is still the possibility of contracting the COVID-19 virus and spreading the virus. Conclusion: Our simulation results provide empirical evidence for health promotion by showing why after fully COVID-19 vaccinated, people are still obliged to implement health protocols. This can be evidence for the government and related agencies to educate the public to be more compliant in implementing health protocols so that we can hope that no one will be infected with the COVID-19 virus and everyone can return to their normal activities